2017
DOI: 10.1177/0042098017696254
|View full text |Cite
|
Sign up to set email alerts
|

Spatial mismatch beyond black and white: Levels and determinants of job access among Asian and Hispanic subpopulations

Abstract: United States (US) based research suggests that distance between residency and employment constrains labour market outcomes for black Americans. Work on this phenomenon, termed spatial mismatch, suggests that residential segregation from whites shapes labour market outcomes among blacks by restricting access to job-dense suburbs. However, few studies examine patterns and drivers of spatial mismatch among Asian and Hispanic subpopulations. Using data on job counts from the 2010 Zip Code Business Patterns data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 41 publications
0
18
1
Order By: Relevance
“…The greatest segregation is among the Korean (0.96), Nepalese (0.88), and Japanese (0.81) communities, followed by White (0.69) and Indian (0.61) enclaves. These segregation levels, particularly among the three most segregated groups, are considerably higher than the results for minority groups in North American cities (e.g., Easley, 2017). For the other South and Southeast Asians, segregation is notably lower (between 0.33 with other ethnicities and 0.49 with Filipinos and Indonesians).…”
Section: Resultscontrasting
confidence: 59%
See 4 more Smart Citations
“…The greatest segregation is among the Korean (0.96), Nepalese (0.88), and Japanese (0.81) communities, followed by White (0.69) and Indian (0.61) enclaves. These segregation levels, particularly among the three most segregated groups, are considerably higher than the results for minority groups in North American cities (e.g., Easley, 2017). For the other South and Southeast Asians, segregation is notably lower (between 0.33 with other ethnicities and 0.49 with Filipinos and Indonesians).…”
Section: Resultscontrasting
confidence: 59%
“…More recently, researchers have extended SMH to consider other vulnerable, minority groups (e.g., low‐income, non‐Black minorities) who are also likely to experience low residential mobility due to discrimination or lack of resources and therefore spatial barriers in accessing employment opportunities (Easley, 2017; Ihlanfeldt, 1993; Liu, 2009), although their experiences may not reflect the typical spatial mismatch scenario proposed by Kain. For example, focusing on Los Angeles, Hu (2019) revealed that the employment conditions of Hispanic and Asians were more sensitive to job accessibility than both White and African American job seekers, hence calling for ethnicity‐specific strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations